EFEKTIVITAS PENGGUNAAN GUAR GUM PADA PEMBUATAN KERTAS ARSIP DARI PULP COTTON LINTER (The Effectiveness of The Use of Guar Gum In Archival Papermaking from Cotton Linter Pulp) - Rina Masriani; Susi Sugesty; Taufan Hidayat; Teddy Kardiansyah (Center for Pulp and Paper, 2016)
The Indonesian Government has set the regulations regarding guidelines for the use of archival paper or permanent document. The paper must meet the specifications of SNI ISO 11108. The problem of archival paper production in Indonesia is difficulty in meeting the quality requirements of permanence and durability. Paper producers in Indonesia have tried to make an archival paper using cotton linter as raw material but it still did not meet the quality requirements of permanence, especially for pH and alkaline reserve parameters. The laboratory archival papermaking experiments using guar gum and high dosage of CaCO3 has been carried out. The scope of experiments: the determination of the characteristics of cotton linter; the determination of optimum freeness of cotton linter, optimum dosage of CaCO3, and optimum dosage of guar gum; the observation of cotton linter pulp and guar gum interaction; the quality testing of archival paper from cotton linter pulp. The results showed that guar gum is effective to improve the folding endurance of paper containing high CaCO3, at least 7.5%. Archival paper produced meets the quality requirements of SNI ISO 11108.Keywords: Archival paper, CaCO3, cotton linter pulp, guar gum ABSTRAK Pemerintah telah menetapkan peraturan mengenai pedoman penggunaan kertas untuk arsip atau dokumen permanen. Kertas arsip harus memenuhi spesifikasi SNI ISO 11108. Permasalahan produksi kertas arsip di Indonesia adalah kesulitan memenuhi syarat mutu permanensi dan durabilitas. Produsen kertas di Indonesia sudah ada yang mencoba membuat kertas arsip dari bahan baku cotton linter, namun belum memenuhi syarat mutu permanensi, yaitu pH dan cadangan alkali. Penelitian pembuatan kertas arsip menggunakan CaCO3 dosis tinggi dan guar gum telah dilakukan. Tahapan penelitian ini yaitu: pengujian karakteristik pulp cotton linter; penentuan freeness optimum, penambahan kadar CaCO3 optimum dan kadar guar gum optimum; pengamatan interaksi pulp cotton linter dan guar gum; pengujian mutu kertas arsip dari pulp cotton linter. Hasil penelitian menunjukkan guar gum efektif untuk meningkatkan parameter ketahanan lipat kertas arsip yang mengandung kadar CaCO3 minimal 7,5%. Kertas arsip yang dihasilkan memenuhi syarat mutu SNI ISO 11108.Kata kunci: kertas arsip, CaCO3, pulp cotton linter, guar gum